2015
DOI: 10.5152/ttd.2015.4584
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis: A Study of 46 Patients from Western India: Clinical Presentations and Survival

Abstract: OBJECTIVES:Idiopathic pulmonary fibrosis (IPF) is the most common form of interstitial lung disease (ILD) diagnosed all over the world as well as in India. The objective was to study the clinical presentations, treatment options, and survival of patients diagnosed with IPF. MATERIALS AND METHODS:This was a 6-year retrospective observational study. All patients diagnosed with ILD underwent a comprehensive evaluation to confirm the diagnosis of IPF and were subsequently included in the study. Clinical data and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
1
1
Order By: Relevance
“…In the present study we found that patients with NSIP had a better survival as compared to patients with IPF. 14 Female predominance was seen in our study which is in contrast with earlier studies 4,8,9,11,[15][16][17] almost all other studies on NSIP; except in the study by Travis et al 5 which showed a male predominance (15 out of 22). The recent systematic review of 12 studies by Travis et al 16 showed that the mean age at presentation was 52 years with age ranged from 26 to 73 years.…”
Section: Discussioncontrasting
confidence: 96%
“…In the present study we found that patients with NSIP had a better survival as compared to patients with IPF. 14 Female predominance was seen in our study which is in contrast with earlier studies 4,8,9,11,[15][16][17] almost all other studies on NSIP; except in the study by Travis et al 5 which showed a male predominance (15 out of 22). The recent systematic review of 12 studies by Travis et al 16 showed that the mean age at presentation was 52 years with age ranged from 26 to 73 years.…”
Section: Discussioncontrasting
confidence: 96%
“…These findings are similar to those found in existing articles from both developing and developed countries. [13,14,[35][36][37] While baseline FVC and FEV1 in this cohort were similar to those found by Collard et al, [37] RV and TLCO were markedly lower in our patients. This adds further evidence to the presence of advanced disease on presentation.…”
Section: Discussionsupporting
confidence: 91%
“…It was observed, for example, in a study from western India, that the median delay in diagnosis of IPF was 20 months, and >20% of patients had wrongly received anti-tuberculosis drugs before they were diagnosed with IPF. [ 10 ] These observations indicate the need to increase awareness of IPF and other ILDs. General practitioners are usually the first point of medical contact and should be trained adequately to differentiate between ILDs from other respiratory disorders, to allow prompt referral of such patients to expert centers.…”
Section: Discussionmentioning
confidence: 99%